How to cheat in Maya 2012 : tools and techniques for character animation - Luhta, Eric (Focal Press, 2012)
The Maya guide for animators, How to Cheat in Maya 2012 presents everything you need to know about character animation in Maya. Fully updated for the latest revision of Maya, this book provides you with complete, step-by-step walkthroughs of essential animation techniques to increase your efficiency and speed. This is an animator's workflow in book form, written by professional animators-not a software book with a few animation pointers thrown in. In addition to all the gold-mine coverage and interviews with expert animators from the previous edition, How to Cheat in Maya 2012 also features a new in-depth chapter on the principles of animation, updated information on camera settings and animation using Maya's new Camera Sequencer tool, the ins and outs of the brand new Editable Motion Trails tool, new techniques for working with characters in multi-shot animation tests and short films, a new cycles chapter covering actions like flying and walks, time-saving scripts, and advanced tricks with the new Graph Editor. The proven "How to Cheat" series gets you up to speed quickly, and in a way that's fun. --The most gorgeous models and lighting will fall flat if the animation is lifeless. Take your animations to the next level with How to Cheat in Maya. Packed with classic animation techniques and insider secrets of a professional animator, this book helps you get things done in the most efficient way possible. --Covers the 12 principles of animation and how they translate into Maya. --Lets readers see "under the hood" of a professional animator's work. Maya explained from a character animator's perspective, a unique and overlooked focus. Luhta is both a teacher and an established professional animator. He has worked on high profile films, commercials, and AAA games. --Companion web site including all exercise/example scene files and extras such as video tutorials, animation files. --Gold-mine coverage, including character animation techniques, working with constraints, foolproof lighting tricks to show off your work, pose to pose blocking, layered animation, constraints, facial animation, fixing gimbal lock, and more. --What's NEW in this edition: Coverage of latest rev of Maya, camera settings and animation, expanded spline reference material with more examples, new techniques for working with characters and props, time-saving scripts, more personality walks, new tricks for lighting and rendering, and additional rigging techniques like bendy arms and more squash and stretch